2021
DOI: 10.16965/ijar.2020.255
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of nutrient foramen in adult human clavicles

Abstract: Introduction: The Clavicle is a modified long bone and only long bone which is placed horizontally and subcutaneously at the root of neck. It transmits the weight from upper limb to the axial skeleton. Nutrient foramen is the largest foramen on the long bones through which nutrient artery for the bones passes. The nutrient artery is the principal source of blood supply to a long bone, particularly important during its active growth period in the embryo and foetus, as well as during the early phase of ossificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…There was no FN in 3 clavicles (3.5%) in our study. Sharmada et al [24] found that there was no FN in 3 of 104 clavicles (2.88%) and Dakshayani et al [7] found that there was no FN in 3 of 100 clavicles (3%), and these ndings are compatible with our study. However, Cihan et al [6] reported that there was no FN in 6 of 61 clavicles (9.8%) and Kumar et al [14] reported that there was no FN in 10 of 102 clavicles (9.8%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There was no FN in 3 clavicles (3.5%) in our study. Sharmada et al [24] found that there was no FN in 3 of 104 clavicles (2.88%) and Dakshayani et al [7] found that there was no FN in 3 of 100 clavicles (3%), and these ndings are compatible with our study. However, Cihan et al [6] reported that there was no FN in 6 of 61 clavicles (9.8%) and Kumar et al [14] reported that there was no FN in 10 of 102 clavicles (9.8%).…”
Section: Discussionsupporting
confidence: 93%
“…Preserving the nutrient artery during surgical reductions and internal xation device applications is important for post-surgical recovery. Additionally, in the development of new transplantation and resection techniques and free vascularized bone grafts, preserving the nutrient artery entering the bone in FN is necessary for surgical success [7]. Therefore, information about the location and number of FN, where the nutrient artery enters the bone tissue, is surgically and clinically important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation